Merajut Kebinekaan Melalui Program “Sadhar Nama” di Sekolah - I Nyoman Tingkat (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2020)
There are a lot of negative issues in Indonesia these last few years which appear in printed media, electronic devices, or even in cyberspace. Issues related to intolerance, radicalism, and child abduction are always there. These issues become more widespeard in the lead up to the political year. Moreover, high school students took part in a demonstration without understanding what substance was being fought. Indonesia seems insecure and uncomfortable in the mass media. Schools should not be silent to face this condition. Schools should appear to educate (enlighten and educate) all educational society so as not to get caught up in issues that spread hatred to divide the unity and integrity of the nation. To respond this condition, SMA N 1 Kuta Selatan develops a program called “Sadhar Nama”. It is an acronym of Buka Puasa bersama (breaking the fast together), Dharma Shanti bersama (one of series to celebrate Nyepi hold in Hindu) , and Natal bersama (celebrating Christmas together). The reason to hold this program is simply to answer challenges over various ethnicity, religion, race, and inter-group relations-based primordial issues which are blown by people who are not responsible for dividing the Unitary Republic of Indonesia. In addition, the acronym “Sadhar Nama” refers to the meaning of identity (nation) as befits a human being and his name. As a representation of the macrocosm that transforms into a microcosm, diverse people in culture with local wisdom values need to be maintained to create a harmonious life within the trihita karana frame. The results obtained from this program are the strengthening of the five main values of the Nation's Character, namely: Religious, Mutual Cooperation, Nationalist, Integrity, and Independence. Strengthening the main value of the character has succeeded in increasing the achievement of SMA Negeri 1 Kuta Selatan. In 2016, SMA N 1 Kuta Selatan won 52 medals, in 2017 won 72 medals, and in 2018 it became 88 medals. In addition, the response to the implementation of the 'Sadhar Nama' Program at SMA Negeri 1 Kuta Selatan was very good with positive responses from 104 respondents (96.29%) out of 108 respondents.